Effects of a fully magnetically levitated centrifugal-flow or axial-flow left ventricular assist device on von Willebrand factor: A prospective multicenter clinical trial - Bansal, Aditya; Uriel, Nir; Colombo, Paolo C; Narisetty, Keerthy; Long, James W; Bhimaraj, Arvind; Cleveland, Jr, Joseph C; Goldstein, Daniel J; Stulak, John M; Najjar, Samer S; Lanfear, David E; Adler, Eric D; et al. (The Journal of heart and lung transplantation, 2019)
Increased shear stress conferred upon the circulation by continuous-flow pumps is associated with hemocompatibility-related adverse events, principally bleeding within the gastrointestinal system, and linked to the degradation of high-molecular-weight multimers (HMWMs) of von Willebrand factor (vWF). We evaluated the structure and functional characteristics of vWF HMWMs in patients with the fully magnetically levitated centrifugal-flow HeartMate 3 (HM3) and the continuous axial-flow HeartMate II (HMII) pump. Findings were correlated with bleeding events. In a prospective, multicenter, comparative cohort study, 60 patients from the Multicenter Study of MagLev Technology in Patients Undergoing Mechanical Circulatory Support Therapy With HeartMate 3 Continued Access Protocol (NCT02892955) with an HM3 pump were compared with 30 randomly selected HMII patients from the PREVENtion of HeartMate II Pump Thrombosis study (NCT02158403) biobank. The primary end point was the difference in the normalized vWF HMWM ratio (ratio of the HMWMs to the intermediate- and low-molecular-weight multimers, normalized to pooled plasma from healthy volunteers) between the HM3 and the HMII pump at 90 days after implantation. Assay tests for vWF activity, vWF antigen, vWF activity to antigen ratio, coagulation factor VIII activity, and ADAMTS13 activity were measured by using standard protocols. Differences in these markers were compared in the context of clinical characteristics and correlated with adjudicated bleeding events within the HM3 group. Of 51 and 29 evaluable patients in the HM3 and HMII arms, respectively, those implanted with the HM3 pump exhibited greater preservation of the vWF HMWM ratio than those with the HMII pump at 90 days after implantation (54.1% vs 42.4%, p < 0.0001). Laboratory values for all vWF assays (antigen, activity, and coagulation factor VIII activity) remained within the normal functional range with no significant differences observed between the pumps at 90 days after implantation. At baseline, there was a decrease in the structural integrity of vWF HMWMs that correlated with increasing heart failure severity as measured by the Interagency Registry for Mechanically Assisted Circulatory Support profile. Multivariable modeling identified the HM3 pump as the only independent variable that determined post-implantation preservation of the structural integrity of vWF HMWMs. This prospective, multicenter comparative analysis study demonstrates that the fully magnetically levitated centrifugal-flow HM3 left ventricular assist device is associated with greater preservation of the structure of vWF HMWMs than the HMII mechanical bearing axial-flow pump.